1999
DOI: 10.1088/0953-2048/12/9/306
|View full text |Cite
|
Sign up to set email alerts
|

The rotational magnetic process and effects of gamma-irradiation on vortex flux pinning in Tl-2223 at low temperatures

Abstract: Magnetization vector measurements were carried out in a polycrystalline sample of Tl-2223 superconductor in fixed fields at low temperatures. Demonstrating the broad distribution in the vortex flux pinning, the vortex flux density B was seen to consist of two component: the rotational component BR turns rigidly with sample rotation and the frictional component BF stays at fixed angle F relative to the applied field H. The pinning torques per vortex were calculated as a function of H at constant temperature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…[12][13][14][15][16][17][18] If this effect were significant, as the rotation proceeded the orientation of the vortices would lag behind the field direction. In an extreme case, vortices deep inside the sample would rotate rigidly with it, a situation that has indeed been observed [19][20][21] . As we will show below, in the present case we have clear experimental evidence that the misorientation between the vortex direction and H due to this lag effect is negligible, so all this complication can be ignored.…”
Section: B Critical Statementioning
confidence: 69%
“…[12][13][14][15][16][17][18] If this effect were significant, as the rotation proceeded the orientation of the vortices would lag behind the field direction. In an extreme case, vortices deep inside the sample would rotate rigidly with it, a situation that has indeed been observed [19][20][21] . As we will show below, in the present case we have clear experimental evidence that the misorientation between the vortex direction and H due to this lag effect is negligible, so all this complication can be ignored.…”
Section: B Critical Statementioning
confidence: 69%
“…For example, Umezawa et al [2] reported an enhancement of the magnitude and reduction of anisotropy of the magnetization current density with slight decrease in the transition temperature in YBCO single crystal due to fast neutron irradiation. Hasan et al [4] observed a considerable increase in the vortex flux pinning in Tl-2223 polycrystals with gamma radiation. Using heavy ion irradiation, Hillmer et al [5] produced columnar defects of different densities and orientations in epitaxial Bi-2212 thin film that increase the normal state resistance and decrease the transition temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Таким образом, излучение влияет на магнитные и транспортные свойства сверхпроводника, и это также означает возможность изменять свойства образца, целенаправленно облучая его частицами различного типа. На практике используется облучение нейтронами [1], протонами [2], электронами [3], γ-квантами [4] и тяжелыми ионами [5]. При этом форма дефекта зависит от энергии и типа облучающих частиц.…”
Section: Introductionunclassified